2022
DOI: 10.1186/s40814-022-01221-x
|View full text |Cite
|
Sign up to set email alerts
|

Person-centred online lifestyle coaching in childhood, adolescent, and young adult cancer survivors: protocol of the multicentre PanCareFollowUp lifestyle intervention feasibility study

Abstract: Background Physical inactivity and unhealthy dietary habits are known to be disadvantageous for the development of late adverse effects in survivors of childhood, adolescent, and young adult cancer. To make interventions, aimed at improving lifestyle, fit into the daily life of survivors, interventions should be designed and delivered in a person-centred way with a limited time burden. As part of the European PanCareFollowUp project, an eHealth intervention was developed to support sustainable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…This contrasts with previous studies on fatigue and lifestyle interventions, showing less enduring effects beyond follow-up periods [ 61 , 64 ]. In upcoming research conducted by Bouwman et al, the investigation will seek to determine whether a lifestyle intervention based on person-centred care principles may yield potential impacts on health behaviours, both in the short-term (i.e., directly following the intervention) and in the longer term (i.e., 4 months post-intervention) [ 65 ]. Exploring sustained effects beyond 4 or 6 months would also be interesting in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…This contrasts with previous studies on fatigue and lifestyle interventions, showing less enduring effects beyond follow-up periods [ 61 , 64 ]. In upcoming research conducted by Bouwman et al, the investigation will seek to determine whether a lifestyle intervention based on person-centred care principles may yield potential impacts on health behaviours, both in the short-term (i.e., directly following the intervention) and in the longer term (i.e., 4 months post-intervention) [ 65 ]. Exploring sustained effects beyond 4 or 6 months would also be interesting in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of consensus regarding an optimal intervention approach is compounded by studies like that of Alchin et al, who found that AYA survivors exhibit limited recall and poor adherence to healthcare recommendations despite the use of a variety of communication modalities for education delivery ( 70 ). In an effort to overcome some of these unique hurdles contemporary investigations are incorporating novel approaches alongside more conventional strategies, such as creating a CCS-directed cookbook and providing guided lifestyle coaching sessions ( 71 , 76 ).…”
Section: Current Intervention Recommendations and Strategiesmentioning
confidence: 99%
“…It has been suggested that CCS, and AYAs in particular, could significantly benefit from such technology-based programs (62). In fact, in recent years CCS studies have increasingly opted for remote (telephone, mobile application, telehealth) intervention strategies as these are typically more cost-effective, accessible to those living in rural and/or remote areas, and preferred among younger groups (60,(68)(69)(70)(71). Nevertheless, Touyz et al found that both adolescents and their parents preferred face-to-face intervention to a web-based one (68).…”
Section: Current Intervention Recommendations and Strategiesmentioning
confidence: 99%